Genética de la resistencia a pudrición causada por Phytophthora tropicalis en dos poblaciones segregantes de yuca (Manihot esculenta Crantz) - Álvarez, E.; Loke, J; Rivera, S.; Llano Rodríguez, Germán Alberto (2002)
Varietal resistance is one of the main tools for managing root rots in cassava, caused by different Phytophthora species, and it is therefore necessary to understand the complexity of the genetic base of this crop. The resistance of parents and progeny of cassava families K (M Nga 2 x CM 2177-2) and CM 9582 (M Bra 1045 x M Cr 81) to Phytophthora tropicalis was evaluated accordingly. Fresh roots of 69 individuals of family K and 43 of family CM 9582 were also inoculated, in addition to the parental materials of each family. Based on the phenotypic evaluation and the molecular map of M Nga 2 (female parent of family K), QTLs associated to the resistance to P. tropicalis were identified and mapped, using simple marker analysis. Cassava family K genotypes, evaluated during 2000 and 2001, showed a percentage of infected root area between 22% and 95%. The correlation between the evaluations of 2000 and 2001 was -0.15. Cassava family CM 9582 genotypes showed an infected area between 70% and 90%. The distribution of frequency of cassava family K genotypes, based on root area affected by P. tropicalis, corresponds to a normal distribution, with one genotype presenting moderate resistance in both years of evaluation, 50 genotypes susceptible, and 17 genotypes highly susceptible. Eight QTLs were defined, two of which accounted for 8.6% and 9% of phenotypic variance. Minor genes were found to control resistance to P. tropicalis.